Relationship between Repeated Sprint Ability and Aerobic Capacity in Professional Soccer Players - Rhys M. Jones; Christian C. Cook; Liam P. Kilduff; Zoran Milanović; Nic James; Goran Sporiš; Bruno Fiorentini; Fredi Fiorentini; Anthony Turner; Goran Vučković (The Scientific World Journal)
Aim. The aim of the present study was to investigate the relationship between maximal aerobic capacity () and repeated sprint ability (RSA) in a group of professional soccer players. Methods. Forty-one professional soccer players (age  yrs, height  cm, weight  kg) were required to perform tests to assess RSA and on two separate days with at least 48 hr rest between testing sessions. Each player performed a treadmill test to determine their and a test for RSA involving the players completing  m sprints (turn after 20 m) with 20 s active recovery between each sprint. Results. There was a significant negative correlation between body mass normalised and mean sprint time () (; ) and total sprint time () (, ). Conclusion. Results of the current study indicate that is one important factor aiding soccer players in the recovery from repeated sprint type activities.